2017
DOI: 10.1038/s41598-017-14065-w
|View full text |Cite
|
Sign up to set email alerts
|

A Brain Penetrant Mutant IDH1 Inhibitor Provides In Vivo Survival Benefit

Abstract: Mutations in IDH1 are highly prevalent in human glioma. First line treatment is radiotherapy, which many patients often forego to avoid treatment-associated morbidities. The high prevalence of IDH1 mutations in glioma highlights the need for brain-penetrant IDH1 mutant-selective inhibitors as an alternative therapeutic option. Here, we have explored the utility of such an inhibitor in IDH1 mutant patient-derived models to assess the potential therapeutic benefits associated with intracranial 2-HG inhibition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 23 publications
0
50
0
Order By: Relevance
“…The IDH1 mut induces changes in the concentration of tricarboxylic acid (TCA) cycle intermediates and lipid metabolites . In vitro and in vivo studies demonstrated that the inhibition of IDH1/2‐mutant enzymes decreases intracellular D‐2‐hydroxyglutarate (D‐2HG) levels and reverses epigenetic dysregulation . Gene expression profiles of large cohorts of glioma and acute myeloid leukemia have shown that IDH1/2 mutant tumors display a distinct gene expression profile enriched for genes expressed in progenitor cells .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IDH1 mut induces changes in the concentration of tricarboxylic acid (TCA) cycle intermediates and lipid metabolites . In vitro and in vivo studies demonstrated that the inhibition of IDH1/2‐mutant enzymes decreases intracellular D‐2‐hydroxyglutarate (D‐2HG) levels and reverses epigenetic dysregulation . Gene expression profiles of large cohorts of glioma and acute myeloid leukemia have shown that IDH1/2 mutant tumors display a distinct gene expression profile enriched for genes expressed in progenitor cells .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 In vitro and in vivo studies demonstrated that the inhibition of IDH1/2-mutant enzymes decreases intracellular D-2-hydroxyglutarate (D-2HG) levels and reverses epigenetic dysregulation. 6,7 Gene expression profiles of large cohorts of glioma and acute myeloid leukemia have shown that IDH1/2 mutant tumors display a distinct gene expression profile enriched for genes expressed in progenitor cells. 8 Metabolic flux analyses have shown that IDH1 mut render tumor cells more dependent on citrate and fatty acids under hypoxia as compared with IDH1 wt cells and this metabolic reprogramming results in decreased cell growth of IDH1 mut cells upon hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction of repressive histone trimethylation markers was identified in cells treated with higher doses of the inhibitor [104]. Murine 440 models showed promising results in terms of tumor growth inhibition and increased survival [104,135,136,139]. However, IDH mutant inhibition did not result in mutant cells growth blockade in other studies, despite effective D2HG levels reduction, suggesting that in some lines tumor growth is indepen-445 dent from IDH mutant function [136,140].…”
Section: Idh Inhibitionmentioning
confidence: 99%
“…As IDH mutation is an early, truncal and stable alteration 425 leading to the production of a specific oncometabolite, the inhibition of the neomorphic enzymatic activity soon appeared as a logic therapeutic approach. Since the first report of an in vitro effective IDH1 R132H inhibitor [104], several other inhibitors targeting also non-R132H IDH1 and IDH2 430 mutations have been developed [135][136][137][138].…”
Section: Idh Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation